Co-creating innovative climate policy frameworks for urban decarbonization: high school engagement in carbon pricing - Ferreira, Lurdes; Dias, Luís P.; Seixas, Júlia; Schmidt, Luísa (Frontiers in Environmental Science, 2025)
IntroductionUrban energy transition requires innovative approaches that make key climate policy tools, such as carbon pricing, actionable and understandable for younger populations and local communities. This study addresses how the co-development of carbon pricing processes in secondary schools can promote CO2 emissions reduction and students’ awareness of their role as agents of change in the community.MethodsAn action research-based case study conducted in a Portuguese public high school with a group of 10th and 11th-grade students, combining a participatory and experiential learning methodology. A participatory action research methodology was applied as the analytical framework. Data collection included quantitative and qualitative surveys and digital logs.ResultsWithin the group, 31% lowered emissions and 7% reported zero emissions by walking, while co-developing a simulation of a carbon pricing mechanism. Students collaborated in assigning an economic value by finding a cost factor based on their experiential learning for the avoided emissions achieved.DiscussionThe approach fostered students’ understanding of carbon pricing while driving measurable reductions in behavior change through commuting-related emission: The students co-created a simplified, context-based model of carbon pricing, reinforcing pro-environmental behavior and offering a model that can inform local climate policy and sustainability goals. The method provides a potential transferable framework for integrating advanced climate policy tools into educational practice.